'Overlap and Interlace': Thoreau’s Thawing Sandbank as Transgenic Artwork - Reder, Kimo (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2019)
In the “Spring” chapter of Walden, Henry David Thoreau’s portrait of a melting, thawing sandbank, as a place of “overlap and interlace”, is a bio-semiotic primal scene. For Thoreau, language itself is an agent of transgenic fusion, finding interlinked roots and common properties at every turn. Thoreau’s wordplay is a page rehearsal for later forms of laboratory-assisted, genre-hopping bio-art in which cross-bred materials form inter-species puns and organic conundrums, phrases from the Old Testament and Descartes are translated via code into DNA base pairs and inserted into plants and bacteria, and gene-splicing becomes a creative act. Using sequencing gels and calipers, autoclaves and plasmid samples, transgenic art plays in the gap between our genes’ lettristic code and manifested matter : Thoreau straddles this same divide with puns and wordplay based on some of the more occult linguistic theories of his day.